INVESTIGATION OF EMPLOYEES MOTIVATION AND EMPLOYEES IN MANUFACTURING COMPANY IN SURABAYA - Tedjokusumo, Edith Primadiana (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2015)
Employee engagement has become a popular topic in Indonesia in the past decade. Based on surveys conducted by several survey institutes in 2012 and 2014, employee engagement has been revealed in Indonesia and shows surprising results over the period. The results of the survey were obtained from answers of various employees from various companies, which led to the possibility of differences in work motivation of each employee. So, this research appears by linking employee work motivation with employee engagement. This study aims to examine the relationship of work motivation with employee attachment to a large manufacturing company in Surabaya. The sample is taken from the total number of employees on a certain unit who is a permanent employee of the company. Measurement using questionnaires with Likert scale. Validity and reliability tests show good results. In addition, there are Test F, Test t and regression analysis. The result of the research shows that there is a correlation between work motivation and employee attachment in general, although in some variables show different result.